I am me, and licuri is small coconut between mindsets, attractions and the little buddha on duty - Guedes, Marcelo Bomfim (Seven Editora, 2023)
This article addresses the relevance of mental attitudes, exploring the distinction between the fixed mindset, characterized by the belief in immutable abilities, and the growth mindset, which promotes the belief in the possibility of development through effort and learning. Based on a comprehensive literature review, the article investigates the philosophical, conceptual and practical origins of mindset, addressing the evolution of human thought throughout history. The influence of ancient Greek philosophers such as the Stoics is examined, highlighting the value of accepting challenges as opportunities for learning and growth. In addition, the Law of Attraction approach is discussed in relation to the growth mindset, emphasizing the importance of maintaining positive thoughts and proactive actions to achieve goals. The influences of religions are also explored, highlighting how Buddhist teachings and the search for self-knowledge can promote personal transformation and continuous development. However, the article also warns about how social comparison and the search for external validation on social media can undermine self-esteem and self-development. Similarly, the superficiality and lack of scientific basis in some self-help books can result in frustration and discourage continuous effort. Based on the concepts revisited, this study concludes on the importance of recognizing both positive and negative sources of influence and adopting a balanced and critical approach to cultivating a mindset that values continuous learning, effort and resilience in the pursuit of goals and personal development. DOI:https://doi.org/10.56238/sevened2023.006-027